Estimating sheet erosion on purple soil hillslope treated with polyacrylamide (PAM) in the Three Gorges Reservoir area - Lun Zhang; Feng Gao; Deyu Liu; Li Wang; Rui Xiang; Chaohuan Ye; Chao Kang; Chang Liu; Hai Xiao; Zhenyao Xia (Journal of Hydrology: Regional Studies, 2023)
Study region: The Three Gorges Reservoir area (TGR), China Study focus: Soil erosion on purple soil hillslope and its negative effects are deleterious to the ecological environment of the TGR. Sheet erosion is the initial form of the slope erosion, which is notably impacted by land degradation, polyacrylamide (PAM) is commonly applied for soil and water conservation purpose, while the sheet erosion on purple soil hillslope treated with PAM remains unclear. New hydrological insights for the region: The findings suggested that the sheet erosion and runoff rate increased as the rainfall intensity was increased and the slope gradient was decreased with increasing PAM application rate until reaching minimum values at 0.80 g m−2, and these quantities increased afterward. The single and combined impacts of the PAM application rate, rainfall intensity and slope gradient on erosion and runoff were significant. The slope gradient, rainfall intensity and PAM application rate also influenced the hydrodynamic parameters, and the stream power was the optimal parameter for describing the sheet erosion. An equation encompassing the rainfall intensity, slope gradient and PAM application rate was used for sheet erosion rate prediction with high accuracy relative to the stream power and PAM application rate. These results could be helpful to better understand sheet erosion on purple soil slopes treated with PAM and offer fundamental guidelines for soil and water conservation in the TGR.